O 'caso José Nogueira': silenciamentos e autoritarismos no pré-1964 e na redemocratização - Oliveira, Raphael Alberti Nóbrega de (2018)
This dissertation intends to present a new version on the death of José Nogueira Leal, a spy of the Navy and journalist of Diário da Noite, a year before the civil-military coup of 1964. In this way, I analyze the death of Nogueira as a political crime and not just as a "police case" associated with the Brazilian Institute of Democratic Action (IBAD) and its affiliated institutes and militants. In the first part of the text I show the search for documents related to Nogueira and IBAD, including my lawsuit against the Civil Police for access to the cadaveric report made by the coroner Manoel Seve Neto. I then make a bibliographic review on the IBAD and analyze the Parliamentary Inquiry Commission in 1963, which found irregularities in this institute. I conclude by approaching the José Nogueira case in detail, reporting behind death scenes and main elements pointed out by the press as beneficiares of the jornalist’s death.